Assessment of the Impacts of Floods in Afghanistan - Peroz, Sharifullah (Journal of Natural Sciences – Kabul University, 2026)
Floods are the quantity of water that overflows the banks of rivers and streams and inundates areas that are usually dry. Afghanistan is a flood-prone country, with flash and riverine floods occurring more frequently. To achieve this, a systematic review was conducted to search international databases, including Google Scholar, ScienceDirect, EM-DAT, and ResearchGate, to collect relevant information on the impact of flood disasters in Afghanistan. The result shows that 89 flood events have occurred in the country since 2000, and the highest number of disasters occurred in 2003 and 2005, with 8 in both years. Heavy, sudden rains were the leading cause of the flooding. However, the total damage cost is not available in the period under consideration. To reduce the impact of floods, relevant government agencies should conduct further research to determine the economic impact of floods on Afghanistan.